Reduction or delay of post-harvest physiological deterioration in cassava roots with higher carotenoid content - Sánchez, T.; Chavez, Alba L.; Ceballos, H.; Rodríguez Amaya, D.B.; Nestel, P; Ishitani, Manabu (2006)
Post-harvest physiological deterioration (PPD) is one of the most important constraints in cassava production and commercialization. It has been hypothesized that the antioxidant properties of carotenoids in yellow cassava roots may help reduce or delay PPD. The industrial sector prefers cassava with a high dry matter content. The latter has also been reported to have a positive correlation with PPD. The objective of this study was to determine the correlation between both the dry matter and total carotenoid contents and PPD in the roots of 101 cassava clones. PPD was positively but weakly associated with dry matter content (R2 = 0.100, P < 0.01), and inversely associated with the total carotenoid content in roots (R2 = 0.515, P < 0.01). In addition, total carotenoid content and color intensity were strongly and positively associated (R2 = 0.769, P < 0.01), suggesting that the roots of cassava clones with a relatively high total carotenoid content can be selected through a simple visual inspection of the color intensity in the parenchyma.